Polymorphic forms of antiandrogenic drug nilutamide: structural and thermodynamic aspects. Issue 16 (15th April 2021) - Surov, Artem O.; Voronin, Alexander P.; Drozd, Ksenia V.; Gruzdev, Matvey S.; Perlovich, German L.; Prashanth, Jupally; Balasubramanian, Sridhar
Abstract : Attempts to obtain new cocrystals of nonsteroidal antiandrogenic drug nilutamide produced alternative polymorphic forms of the compound (Form II and Form III) and their crystal structures were elucidated by single-crystal X-ray diffraction. Abstract : Attempts to obtain new cocrystals of nonsteroidal antiandrogenic drug nilutamide produced alternative polymorphic forms of the compound (Form II and Form III) and their crystal structures were elucidated by single-crystal X-ray diffraction. Apart from the cocrystallization technique, lyophilization was found to be an effective strategy for achieving polymorph control of nilutamide, which was difficult to obtain by other methods. The physicochemical properties and relative stability of the commercial Form I and newly obtained Form II were comprehensively investigated by a variety of analytical methods (thermal analysis, solution calorimetry, solubility, and sublimation), whereas for Form III, only a handful of experimental parameters were obtained due to the elusive nature of the polymorph. Form I and Form II were found to be monotropically related, with Form I being confirmed as the thermodynamically most stable solid phase. In addition, the performance of different DFT-D and semi-empirical schemes for lattice energy calculation and polymorph energy ranking was compared and analysed. Lattice energy calculations using periodic DFT at B3LYP-D3/6-31(F+)G(d, p) and PBEh-3c/def2-mSVP levels of theory were found to provide the most accurate lattice energy values for Form I against experimental data, while PIXEL and PBEh-3c/def2-mSVP were the only methods that predicted the correct order of stability of Forms I and II.